Surfactant-free synthesis of pdcu bimetallic foam and its catalytic reduction for 4-nitrophenol - Jun Liu; Honggui Xiang; Jing Yang; Xianze Liu (Environmental Science and Pollution Research, 2026)

Mechanism of deep and selective sulfate removal from high-concentration CaCl2 solutions via porous interfacial deposition on calcium-modified carbon - Ghulam Mustafa; Zhe Zhang; Honggui Liu; Zhen Chen; Zihong Cheng; Cheng Yang; Shuqin Liu; Feilong Liang; Yong Guo; Guodong Wan; Niyazi Abulaizi; Wei Ma (Journal of Cleaner Production, 2026)

Early maternal separation induced spatial memory deficits through hippocampal inflammation in piglets - Qi Han; Baochen Xie; Yuxi Shen; Ting Wei; Wenhui Zhang; YongJian Cui; Honggui Liu; Shuai Liu (Applied Animal Behaviour Science, 2026)

A lightweight model of dual - backbone real-time detection transformer for pig body temperature detection and its onsite validation - Jinghan He; Hong Zhou; Qiuju Xie; Wenwu Wang; Xuefei Liu; Wenyang Liu; Yuhuan Guo; Honggui Liu (Computers and Electronics in Agriculture, 2026)

Potential toxic effects of polylactic acid microplastics accumulation on multiple tissue structures and hematology in carp - Sitong Zhou; Zhonghui Wang; Xuanning Liu; Mengyao Wu; Yamiao Fan; Bo Ma; Yutao Li; Houjuan Xing; Honggui Liu (Environmental Pollution, 2026)

Feeding behavior recognition of group-housed pigs based on pose estimation and keypoint features discrimination - Yuhang Hu; Xin Dai; Baisheng Dai; Ran Li; Junlong Fang; Yanling Yin; Honggui Liu; Weizheng Shen (Computers and Electronics in Agriculture, 2025)

Loofah-inspired biomimetic scaffold with triaxial anisotropy for spatiotemporally guided cortical-cancellous bone reconstruction - Shuai Fan; Junlong Zhong; Jiachao Xiong; Fanrong Ai; Honggui Yu; Zhiming Liu; Wen Tan; Qin Wu; Zhenhai Zhou; Jing Yang; Kai Cao (Chemical Engineering Journal, 2025)

Research on the grease rear penetration escape behavior and the sealing performance of shield tail under static pressure of shield tail brush - Zhanlin Cao; Shunhua Zhou; Jianguo Liu; Huiji Guo; Honggui Di (Tunnelling and Underground Space Technology, 2025)

Collaborative knowledge transfer-based multiobjective multitask particle swarm optimization - Yushuang Wang; Zheng Liu; Honggui Han (Swarm and Evolutionary Computation, 2025)

The group-modified nanoplastics bring higher risk on promoting the antibiotic resistance genes dissemination by stimulate bacteria to generate more ROS under aerobic condition - Chenxi Li; Yang Liu; Linjie Wang; Qi Dai; Zhe Piao; Ya Zhang; Honggui Wang (Journal of Environmental Chemical Engineering, 2025)

Multi-behavior detection of group-housed pigs based on YOLOX and SCTS-SlowFast - Ran Li; Baisheng Dai; Yuhang Hu; Xin Dai; Junlong Fang; Yanling Yin; Honggui Liu; Weizheng Shen (Computers and Electronics in Agriculture, 2024)

Deep neural network with adaptive dual-modality fusion for temporal aggressive behavior detection of group-housed pigs - Kai Yan; Baisheng Dai; Honggui Liu; Yanling Yin; Xiao Li; Renbiao Wu; Weizheng Shen (Computers and Electronics in Agriculture, 2024)

Influence of anionic polyacrylamide on the freeze–thaw resistance of silty clay - Jiale Yang; Shuangyang Li; Honggui Di; Deren Liu; Xu Wang; Yongchun Zhao (Cold Regions Science and Technology, 2024)

Structures, issues, and optimization strategies of Ni-rich and Co-low cathode materials for lithium-ion battery - Honggui Xie; Huarong Peng; Dongting Jiang; Zhe Xiao; Xueping Liu; Hao Liang; Mingli Wu; Dongming Liu; Yun Li; Yiling Sun; Shengkui Zhong; Zhengfang Qian; et al. (Chemical Engineering Journal, 2023)

Organic Selenium Alleviates Ammonia-Mediated Abnormal Autophagy by Regulating Inflammatory Pathways and the Keap1/Nrf2 Axis in the Hypothalamus of Finishing Pigs - Jianxing Wang; Jing Wang; Yutao Li; Qi Han; Yulai Wang; Honggui Liu; Jun Bao (Biological Trace Element Research, 2023)

Comparison of Growth Performance and Muscle Nutrition Levels of Juvenile Siniperca scherzeri Fed on an Iced Trash Fish Diet and a Formulated Diet - Maoyuan Wang; Mingyong Lai; Tian Tian; Meiying Wu; Yinhua Liu; Ping Liang; Liuting Huang; Zhiqing Qin; Xiaojun Ye; Wei Xiao; Honggui Huang (Fishes, 2023)
To assess the possibility of using a formulated diet instead of an iced trash fish diet for feeding spotted mandarin fish (Siniperca scherzeri), a 20-week feeding trial was conducted. The objective of the study was to examine the effects of the formulated diet (FG) and the iced trash fish diet (XG) on the growth performance and muscle nutrient composition of the fish. The results showed that the spotted mandarin fish fed with an XG had slightly higher survival rates, weight gain rate, fullness, hepatic index, and viscera index compared to those fed with an FG, although the differences were not significant (p > 0.05). Additionally, in terms of muscle composition, the FG group had higher levels of crude protein and ash content in the fish muscle compared to the XG group (p

Selenium Alleviates Ammonia-Induced Splenic Cell Apoptosis and Inflammation by Regulating the Interleukin Family/Death Receptor Axis and Nrf2 Signaling Pathway - Jing Wang; Yutao Li; Jianxing Wang; Yulai Wang; Honggui Liu; Jun Bao (Biological Trace Element Research, 2023)

The in situ catalytic oxidation of sulfamethoxazole via peroxydisufate activation operated in a NG/rGO/CNTs composite membrane filtration - Feiyue Qian; Honggui Yin; Feng Liu; Jiayi Sheng; Shiqian Gao; Yaoliang Shen (Environmental Science and Pollution Research, 2021)

Selenium Deficiency Induces Inflammation via the iNOS/NF-κB Pathway in the Brain of Pigs - Yilei Zhang; Jiawen Cui; Yingfei Lu; Chunzheng Huang; Honggui Liu; Shiwen Xu (Biological Trace Element Research, 2020)

Chlorpyrifos induces redox imbalance‐dependent inflammation in common carp lymphocyte through dysfunction of T‐cell receptor γ - Jie Yang; Yafan Gong; Jingzeng Cai; Yingying Zheng; Honggui Liu; Ziwei Zhang (Journal of Fish Diseases, 2020)
Chlorpyrifos is a poisonous pesticide that is highly toxic to fish and aquatic organisms. However, there are fewer reports about how chlorpyrifos influences the redox balance of immune cells. Herein, the head kidney tissue treated with chlorpyrifos to do transcriptome analysis and TCR γ was screened out. Subsequently, we established TCR γ knockdown and overexpression carp head kidney lymphocyte models, respectively, by using RNA interference and pcDNA3.1. Real‐time PCR, fluorescent staining, oxidation and antioxidant kit were used to detect the related factors. We found that TCR γ knockdown significantly increased the mRNA expression of HSP70 and HSP90 and decreased the mRNA expression of SOD and CAT. Meanwhile, TCR γ knockdown reduced the activities of GSH, GSG‐PX, T‐AOC, CAT and SOD and increased the content of MDA and H 2 O 2 and activities of iNOS. Adverse results were obtained in TCR γ overexpression group. Additionally, TCR γ knockdown significantly increased the mRNA expression of IFN‐γ, IL‐1β, IL‐8, IL‐10, Nrf2 and NF‐κB, but relieved TCR γ overexpression, in which the process of inflammation was activated. Our results reported here indicated that chlorpyrifos induces redox imbalance‐dependent inflammation in common carp lymphocyte through dysfunction of T‐cell receptor γ, and HSPs play potential protective role in entire process.

Involvement of MEM1 in DNA demethylation in Arabidopsis - Yanke Lu; Jie Dai; Liu Yang; Yumei La; Shaoxia Zhou; Sheng Qiang; Qianqian Wang; Feng Tan; Yufeng Wu; Weiwen Kong; Honggui La (Plant Molecular Biology, 2020)

Analysis of the DNA methylation patterns and transcriptional regulation of the NB-LRR-encoding gene family in Arabidopsis thaliana - Weiwen Kong; Bin Li; Qianqian Wang; Bin Wang; Xiaoke Duan; Li Ding; Yanke Lu; Li-Wei Liu; Honggui La (Plant Molecular Biology, 2018)